SUSTAINABLE ENERGY EDUCATION THROUGH IOT-BASED PLTS KIT TRAINING AND MENTORING AT SMAN 3 SINGKAWANG - Aula, Abqori; Syaifurrahman, Syaifurrahman; Suryadi, Dedy; Tjahjamooniarsih, Neilcy; Husin, Fitriah (Universitas Padjadjaran, 2025)
The integration of Internet of Things (IoT) technology into training and mentoring programs for Photovoltaic Power System (PLTS) kits can significantly enhance the education of renewable energy, particularly in West Kalimantan, Indonesia. The partner in this community service program is State High School 3 of Singkawang City, West Kalimantan. The purpose of this community service is both to educate on the use of IoT for monitoring PLTS kits and to educate high school students about renewable energy. This approach involves classical teaching and hands-on learning, which enables real-time monitoring and data analysis, making it more effective and engaging for students. The method used in this service consists of the preparation stage, the implementation stage, and the evaluation stage. Within the preparation stage, PLTS kits were designed and constructed with an embedded IoT module. The implementation stage involved socialization about new and renewable energy as well as the trend in IoT, followed by hands-on training for participating students using the PLTS kits. There were about 20 students and a couple of accompanying teachers. The results of the evaluation stage show that the student participants were happily thrilled with the hands-on training, and the teachers were satisfied with the mentoring program.Integrasi teknologi Internet of Things (IoT) ke dalam program pelatihan dan pendampingan untuk kit Sistem Tenaga Fotovoltaik (PLTS) dapat secara signifikan meningkatkan pendidikan energi terbarukan, khususnya di Kalimantan Barat, Indonesia. Mitra dalam program pengabdian masyarakat ini adalah SMA Negeri 3 Kota Singkawang, Kalimantan Barat. Tujuan dari pengabdian masyarakat ini adalah untuk mendidik penggunaan IoT untuk memantau kit PLTS dan juga untuk mendidik siswa sekolah menengah tentang energi terbarukan. Pendekatan ini melibatkan pengajaran klasikal dan pembelajaran langsung yang memungkinkan pemantauan waktu nyata, dan analisis data, sehingga lebih efektif dan menarik bagi siswa. Metode yang digunakan dalam layanan ini terdiri dari tahap persiapan, tahap implementasi, dan tahap evaluasi. Dalam tahap persiapan, kit PLTS dirancang dan dibangun dengan modul IoT yang tertanam. Tahap implementasi melibatkan sosialisasi tentang energi baru dan terbarukan serta tren di IoT, diikuti oleh pelatihan langsung bagi siswa yang berpartisipasi menggunakan kit PLTS. Ada sekitar 20 siswa dan beberapa guru pendamping. Hasil tahap evaluasi menunjukkan bahwa para peserta siswa merasa gembira dan gembira dengan pelatihan praktik, sedangkan para guru merasa puas dengan program bimbingan.